Based on theoretical design simultaneous analysis of multiple neonicotinoid pesticides in beeswax by deep eutectic solvents extraction combined with UHPLC-MS/MS - Guodong Mu; Sha Yan; Fei Pan; Haitao Xu; Xu Jing; Xiaofeng Xue (Food Chemistry: X)
Beeswax, an FDA-approved component, has been extensively applied in feed, pharmaceutical, and food industries. The occurrence of neonicotinoid pesticides in beehive systems and their residues in beeswax have caused safety risks. Therefore, establishing a detection method for neonicotinoid pesticide residues in beeswax is crucial for ensuring its quality. The superhydrophobic property of beeswax makes it a challenge to develop suitable determination methods. In this work, we determined Proline and Oxalic acid as a suitable deep eutectic solvent (DES) to extract neonicotinoids from beeswax through theoretical design and verification tests. Systematic molecular dynamics simulations confirmed that hydrogen bonding and van der Waals forces facilitate the migration of neonicotinoid pesticides from beeswax into the DES. Performance analysis of the method revealed that the DES extraction combined with UHPLC-MS/MS approach exhibited excellent detection capabilities. It was applied to real beeswax sample analysis with the characteristics of simpleness, quickness, environmental friendliness, and high throughput.